The Black Ghost : hard revolution - Gallagher, Monica, 1979-; Segura, Alex, 1980- (Dark Horse Books, 2021)
"Meet Lara Dominguez--a troubled Creighton cops reporter obsessed with the city's debonair vigilante the Black Ghost. With the help of a mysterious cyberinformant named LONE, Lara's inched closer to uncovering the Ghost's identity"--